An Experimental Investigation and Numerical Analysis on The Behavior Of Reinforced Concrete Thick Slabs under Static Loading - Kh. Yousif, Yousif; S. Ali, Ahmad; A. Al-Azzawi, Adel (Iraqi Journal of Civil Engineering, 2017)
This paper presents the testing results and numerical results of nine reinforced concrete thick slabs with and without openings. All slab specimens have the same planar dimensions (1000mm×1000mm) with three different thicknesses of (120mm,100mm,and 80mm).The slabs resting on 4 corner steel columns and tested under concentrated static loading up to failure. These slabs were also analyzed using nonlinear finite element method assuming nonlinear material properties. From the experiments, it was found that, The presence of openings in slabs supported on their four corners decreases the strength and rigidity of slabs to about (12-23) % depending on the slab thicknesses and the shape of these openings. The slabs with (circular opening) recorded a reduction in ultimate strength to about(20) % from those with square openings having an equivalent opening areas. The yielding of main steel reinforcement occurred at load about 85% of the slab ultimate load. The ultimate loads predicted by ANSYS model have showed a good agreement with the experimental results.